Peningkatan Kreativitas Dan Keterampilan Anak Usia 9 – 11 Tahun Melalui Eksplorasi Kolase Pada Gambar Di Sanggar Kosmi Jagakarsa - Nahlia Hendra, Laynafira; Tridjata Suprabanindya, Caecilia (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
Research at Sanggar Kosmi refers to the need for innovation in improving children's creativity and skills at Sanggar Kosmi. The child participants did not show their creativity and skills optimally because the results of their work only focused on predetermined objects. This research aims to increase children's imagination, creative potential and skills in creating fine arts, understand the quality of learning in collage media using the exploration method carried out at Sanggar Kosmi, provide new experiences regarding variations in collage work on images, develop the effectiveness of Handout and PPT media as well as the PjBL learning model in collage learning activities on pictures. The research used descriptive qualitative methods with 5 participants. The assessment of collage works on images is divided into 4 categories, namely: very good category, good category, quite good category, and poor category. There are 10 students' works in the activity of making collages on images using natural and synthetic materials. The results of this research show that the ability to make collages on pictures in children aged 9-11 years at Sanggar Kosmi is quite successful in exploring collage materials and techniques, as well as the use of the PjBL model using Handouts and theme development PPTs is very helpful in the learning process, so it needs to be developed again further so that it can be studied by many groups and become a learning or training activity that can be recommended as a useful activity.